ANALISIS KUALITAS PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN LANJUT USIA DI PUSKESMAS KEBUN SIKOLOS KOTA PADANG PANJANG - Handoko, Bobi; Angella, Shelly; pramita, cindi febriani (LPPM Universitas Awal Bros, 2023)
The quality of service can be said to be good if the service provided is in accordance with or more than the patient's expectations so that it can be said to be satisfactory. On the other hand, services that are not as expected by the patient can make the patient dissatisfied. At the Kebun Sikolos Health Center in Padang Panjang City, 3 out of 7 elderly patients were satisfied with the services provided by the health workers at the Kebun Sikolos Health Center, Padang Panjang City. The purpose of this study was to determine the quality of health services on the satisfaction of elderly patients at the Kebun Sikolos Health Center, Padang Panjang City. This study uses a quantitative type of research using a descriptive design, carried out at Kebun Sikolos Health Center with 51 elderly patients as respondents. The results of the study can be seen from the level of satisfaction of elderly patients with high satisfaction with a value range of 92.2%. It can be said that there is an effect of service quality on patient satisfaction, in line with the results of good service quality. In the assessment of services using five dimensions, most of the elderly patients rate well on the dimensions of Reliability (Reliability) with a range of 64.7%, Responsiveness with a range of 47.1%, Assurance of 41.2%, and Empathy. (Empathy) of 68.6% . However, on the Physical Evidence (Tangible) variable, the majority of elderly patients rated less with a range of 52.9%. The conclusion of the study can be said that the quality of service at the Kebun Sikolos Health Center is good, it can be proven by the high satisfaction of elderly patients. Here it can be said that there is an influence of service quality on patient satisfaction, in line with the results of good service quality.